Enriched environment protects the nigrostriatal dopaminergic system and induces astroglial reaction in the 6-OHDA rat model of Parkinson's disease - Anastasia Gonzalez, Agustin (2009)
Enriched environment (EE) is neuroprotective in several animal models of neurodegeneration. It stimulates the expression of trophic factors and modifies the astrocyte cell population which has been said to exert neuroprotective effects. We have investigated the effects of EE on 6-hydroxydopamine (6-OHDA)-induced neuronal death after unilateral administration to the medial forebrain bundle, which reaches 85-95% of dopaminergic neurons in the substantia nigra after 3 weeks. Continuous exposure to EE 3 weeks before and after 6-OHDA injection prevents neuronal death (assessed by tyrosine hydroxylase staining), protects the nigrostriatal pathway (assessed by Fluorogold retrograde labeling) and reduces motor impairment. Four days after 6-OHDA injection, EE was associated with a marked increase in glial fibrillary acidic protein staining and prevented neuronal death (assessed by Fluoro Jade-B) but not partial loss of tyrosine hydroxylase staining in the anterior substantia nigra. These results robustly demonstrate that EE preserves the entire nigrostriatal system against 6-OHDA-induced toxicity, and suggests that an early post-lesion astrocytic reaction may participate in the neuroprotective mechanism.